Sophie et Julie : Une formation impossible ? - Gianni Iotti (Revue Italienne d'Etudes Françaises, 2023)
The article draws a parallel between the two “récits de formation” that can be found, respectively, in Émile and in La Nouvelle Héloïse. In the pedagogical treatise, Sophie is presented to the reader as someone naturally endowed with the social and psychological characteristics functional to her encounter with Émile, and the story ends with the description of the two young people’s conjugal happiness. The novel, on the other hand, takes Julie on a painful journey of amorous sublimation and renunciation; despite its stated aims, the work culminates in the protagonist’s death and the desolation of all the other characters. From this point onwards, we can see that, as far as the theme of formation is concerned, the novel elaborates a vision of things that is much more complex than the one developed by the pedagogical discourse: Julie’s final death belies the possibility of the formative journey of a woman who has renounced love-passion in order to sublimate it into family and social love, according to the thesis of the Émile. What Rousseau maintains as a philosopher he disavows as a novelist.